Advancing women in business : the calalyst guide : best practices from the corporate leaders (Jossey-Bass Pub. San FranciscoUS)
Targets organizations that are contemplating change initiatives for women's advancement. Presents principles and practical methods for retaining and advancing women in business. Suggests best practices including: development of communication and teams in order to promote an inclusive job culture; ensuring women's advancement into senior corporate leadership; formation of workplace networks; and zero tolerance sexual harassment policy and training.
Located in the Learning Resource Centre